The Progression of Interstitial Fibrosis and Tubular Atrophy at 6 Months Is an Independent Predictor of Poor Graft Outcomes in Kidney Transplant Recipients. Issue 12 (4th November 2022) - Ouellet, Gabriel; Houde, Isabelle; Riopel, Julie; Latulippe, Eva; Douville, Pierre; Lesage, Julie; Côté, Isabelle; Lapointe, Isabelle; De Serres, Sacha A.
Abstract : Background: Interstitial fibrosis and tubular atrophy (IFTA) found on 1-y surveillance biopsies has been associated with poor graft outcomes. However, its progression over time and relationship to outcomes are less well defined. Methods: We studied implantation and 6-mo surveillance biopsies and examined the association between the progression of IFTA (ΔIFTA) and a composite of censored graft loss or doubling of serum creatinine in 248 adult kidney recipients. Results: The percentage of patients with ΔIFTA of 1 or ≥2 was 35% and 22%, respectively. Positive ΔIFTA was a risk factor for the composite endpoint (hazard ratio, 1.36; 95% confidence interval, 1.03-1.79). This estimate was robust to adjustment for recipient and donor baseline characteristics, baseline IFTA, tacrolimus levels, and rejection status. ΔIFTA was associated with decreased estimated glomerular filtration rate at 3 and 5 y. IFTA+i was a predictor in the cohort; however, IFTA progression was not limited to those with a mononuclear cell interstitial inflammation (Banff "i") score above zero. Notably, donor age was a predictor of IFTA at 6 mo, but not of ΔIFTA, whereas rejection, donor diabetes, and recipient smoking status were. Conclusions: Progression of IFTA at 6 mo can predict outcomes. ΔIFTA was not related to donor age but may be linked to other risk factors influencing decision-making for donor versus recipient selection. Abstract :